Phentermine and topiramate combination for chronic weight management: a review - Gupta, Kanchan; Chopra, Geetak; Kaushal, Sandeep (International Journal of Basic & Clinical Pharmacology, 2017)
Obesity is a major public health concern and one of the leading preventable causes of death worldwide. It has manifold adverse health consequences, potentially involving all major organ systems thus leading to a reduced life expectancy. The long-term successful management of obesity remains a herculean task and invariably requires a multifaceted approach including lifestyle and behavioral modification, increased physical activity, and adjunctive pharmacotherapy and bariatric surgery. However, effective pharmacological options are limited because of the previous history of several failed agents as well as the fact that presently available agents are few, and utilized only as monotherapy. The recent Food and Drug Administration (FDA) approval of the fixed drug combination of phentermine and extended release topiramate marks the first FDA approved combination pharmacotherapeutic agent for obesity. This review details the various pharmacological aspects of the use of phentermine and topiramate combination along with the results of clinical trials done so far and also the present role of this combination in the management of obesity. Beyond the significant improvement in weight, the findings from various clinical trials also show improvement in metabolic and glycemic parameters, blood pressure, and lipid profile suggesting its added utility in cardiovascular risk modification. The acceptability of this combination would usher in a new era in the pharmacotherapy of obesity that utilizes combination therapy to improve efficacy, enhance synergism and concurrently minimize the risk of adverse effects. As with any newly marketed drug, there may be yet-unknown benefits and risks associated with this combination, which would be known only after its long-term use.